The 18th International Conference on Experimental Mechanics 2018
DOI: 10.3390/icem18-05394
|View full text |Cite
|
Sign up to set email alerts
|

Fast Assessment of Post-Fire Residual Strength of Reinforced Concrete Frame Buildings Based on Non-Destructive Tests

Abstract: Assessment of the residual strength of reinforced concrete buildings subjected to fire is a problem that many times requires a very fast resolution that is necessary for the action of firemen and/or for forensic fire investigation and/or structural assessment of post-fire condition of the building: in all cases safety and integrity of firemen and researchers can be at risk, and it is necessary to have quick and sufficiently reliable information in order to choose whether enter freely, enter with caution or sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(10 reference statements)
0
2
0
Order By: Relevance
“…It would be essential to develop guidelines/methodology for assessment of fire-ravaged concrete structures for Indian scenarios. There have been few reports of evaluation of the condition of the fire-affected members [82] and structures [83] in India as well as abroad [84][85][86]. Further such studies are indicated for India in coming years.…”
Section: Assessment Of Fire-ravaged Concrete Structures With Non-destmentioning
confidence: 99%
“…It would be essential to develop guidelines/methodology for assessment of fire-ravaged concrete structures for Indian scenarios. There have been few reports of evaluation of the condition of the fire-affected members [82] and structures [83] in India as well as abroad [84][85][86]. Further such studies are indicated for India in coming years.…”
Section: Assessment Of Fire-ravaged Concrete Structures With Non-destmentioning
confidence: 99%
“…It is well known that concrete at elevated temperature brings a significant loss of mechanical properties such as compressive strength, tensile strength, and elastic modulus. 1,2 The strength assessment of concrete for fire-damaged concrete structures is important for a decision of remodeling, repairing, strengthening, or demolishing of concrete structures. Therefore, a reasonable strength assessment of concrete after subjected to fire is very important work for structural sustainability of the fire-damaged concrete structures.…”
Section: Introductionmentioning
confidence: 99%